PARP1 Links CHD2-Mediated Chromatin Expansion and H3.3 Deposition to DNA Repair by Non-homologous End-Joining - Luijsterburg, Martijn S. (Mol Cell, 2016)
The response to DNA double-strand breaks (DSBs) requires alterations in chromatin structure to promote the assembly of repair complexes on broken chromosomes. Non-homologous end-joining (NHEJ) is the dominant DSB repair pathway in human cells, but our understanding of how it operates in chromatin is limited. Here, we define a mechanism that plays a crucial role in regulating NHEJ in chromatin. This mechanism is initiated by DNA damage-associated poly(ADP-ribose) polymerase 1 (PARP1), which recruits the chromatin remodeler CHD2 through a poly(ADP-ribose)-binding domain. CHD2 in turn triggers rapid chromatin expansion and the deposition of histone variant H3.3 at sites of DNA damage. Importantly, we find that PARP1, CHD2, and H3.3 regulate the assembly of NHEJ complexes at broken chromosomes to promote efficient DNA repair. Together, these findings reveal a PARP1-dependent process that couples ATP-dependent chromatin remodeling with histone variant deposition at DSBs to facilitate NHEJ and safeguard genomic stability.